Using Stronge Teacher Evaluation System to Assess the Effectiveness Level of Mr. Brown as an EFL Teacher in the Mind Your Language TV Show: An Attempt to Validate a Reflective Tool to Train Preservice EFL Teachers - Lasekan, Olusiji (Frontiers in Psychology, 2021)
To develop a reflective tool for promoting teacher effectiveness among preservice EFL teachers, this paper seeks to investigate the effectiveness degree of an EFL teacher as it is being depicted in a popular TV show. This is conducted using the Stronge teacher evaluation system to assess the main character's level of effectiveness as an EFL teacher (Mr. Brown) in the Mind Your Language TV Show. Drawing upon the intersection of the character's effectiveness within the framework of characterization, representation, and perceived realism theory, a qualitative research method involving seven performance indicators of the Stronge teacher evaluation system was adopted to assess the main character. The findings showed that the character is a highly effective EFL teacher because his personal and professional characteristics are evidenced in the evaluation system's seven performance standards. This suggests that the Show can be used as a reflective tool by preservice EFL teachers to construct and enhance their professional identities and instructional practices. This work contributes to the existing knowledge of teachers' representation in movies and its implication in preservice EFL education by providing the first study on the representation of EFL teachers in a TV show. A future research direction is also presented.